2019
DOI: 10.1128/msystems.00021-19
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Intestinal Microbiota on Colonization Resistance to Salmonella and the Shedding Pattern of Naturally Exposed Pigs

Abstract: Salmonella colonization and infection in production animals such as pigs are a cause for concern from a public health perspective. Variations in susceptibility to natural infection may be influenced by the intestinal microbiota. Using 16S rRNA compositional sequencing, we characterized the fecal microbiome of 15 weaned pigs naturally infected with Salmonella at 18, 33, and 45 days postweaning. Dissimilarities in microbiota composition were analyzed in relation to Salmonella infection status (infected, not infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 65 publications
8
47
1
Order By: Relevance
“…In fact, we have described an increased abundance of Prevotella, Coprococcus, and Paraprevotella in Salmonella-positive animals, which is in accordance with studies carried out in experimental Salmonella challenges [9,12,45]. Moreover, the fecal microbiota of negative pigs showed a higher abundance of Ruminococcaceae compared to the Salmonella-positive pigs, which is also in accordance with the literature [8,9,11]. Interestingly, our results showed that Salmonella-positive pigs had higher beta diversity compared with negative animals, meaning that Salmonella-positive pigs had more heterogeneous gut microbiota.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In fact, we have described an increased abundance of Prevotella, Coprococcus, and Paraprevotella in Salmonella-positive animals, which is in accordance with studies carried out in experimental Salmonella challenges [9,12,45]. Moreover, the fecal microbiota of negative pigs showed a higher abundance of Ruminococcaceae compared to the Salmonella-positive pigs, which is also in accordance with the literature [8,9,11]. Interestingly, our results showed that Salmonella-positive pigs had higher beta diversity compared with negative animals, meaning that Salmonella-positive pigs had more heterogeneous gut microbiota.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, we observed that the phyla Bacteroidetes and Firmicutes were dominant in the fecal microbiota of finishing pigs. These two taxa accounted for 90% of all the sequences obtained, like in prior studies examining the gut microbiota of pigs [8,9,11,[38][39][40]. Moreover, the fecal core microbiota we uncovered was consistent with previous studies in pigs [41][42][43][44].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations